Brand religion : shen a new light on today's marketing beliefs - Pallini, Katia, 1987-; De Wulf, Kristof, ....- (S.l. : Insites Consulting)
Since the early days of business, marketing gurus have preached their beliefs on how to build strong brands. These theories and models have been translated into numerous books to provide a clear framework for marketers on what to aim for and how to grow their band. But in this abundance of models and theories, marketers might find themselves lost in translation. The Brand Religion paper aims aim to simplify the world of marketing in three main Brand Religions beyond the classic 'Kotler-ian' thinking. Discover the core beliefs behind each of these Brand Regions and, togheter with relevant case study examples, find out how to track the different performance metrics that go hand in hand with these models.
Keywords: marketing ; merken